Systematic Approach to Teaching Academic Writing: Practical Experience - I. E. Abramova; A. V. Ananyina (Высшее образование в России)
The article describes the practical implementation of an experimental model for teaching academic writing to non-linguistic students of humanities at three levels of higher education. Improving the quality of domestic scientific publications submitted to high-ranking journals requires new effective pedagogical technologies. Theory and methodology analysis, as well as empirical observations show that the problems faced by Russian-speaking authors of academic texts can be divided into two categories: strong Russian accent that creates the language barrier and hinders understanding, and flawed academic style that leads to the cross-cultural academic barrier. The described ten-year study involved 25 students of Petrozavodsk State University, aged 17 to 28, who subsequently completed bachelor’s, master’s and postgraduate programs. At each of the three stages, the participants completed a set of tasks aimed at consistent and systematic formation of academic writing competence through writing abstracts (bachelors), conference proceedings (master’s students) and full-text academic articles (postgraduate students). To collect and process the data, the researchers used an open-ended questionnaire, the observation method, expert assessment, and descriptive statistics. The study results showed that the systematic approach helps to effectively eliminate structural and stylistic writing problems over the course of studies. However, the difficulties associated with the manifestation of the Russian accent in written English-language academic discourse are more resistant. The authors make the conclusion that the systematic development of academic writing skills in English will help to overcome obstacles for the internationalization of Russian science.